Forest-based adaptation: transformational adaptation through forests and trees - Libert-Amico, A.; Duchelle, Amy E.; Cobb, A.; Peccoud, V.; Djoudi, H. (Food and Agriculture Organization of the United Nations, 2022)
Forest-based adaptation is an ensemble of climate actions that employ forests and trees in support of climate change adaptation and resilience, including sustainable forest management, forest conservation and restoration, reforestation and afforestation. Forest-based adaptation can help address the gaps between current adaptation actions and the adaptation needed for reducing climate-related risks and impacts, while contributing to most of the Sustainable Development Goals and promoting strong synergies with mitigation. This FAO technical paper unpacks the concept of forest-based adaptation and describes policy spheres that could bolster the role of forests and trees in providing adaptation and resilience benefits. It introduces a set of ten principles for using forests and trees to promote transformational adaptation, which were developed with leading experts from the Center for International Forestry Research and World Agroforestry (CIFOR-ICRAF) and other partners. It describes the policy implications of each principle and draws on examples from diverse forest ecosystems and management practices to illustrate their application in practice.